Gender equality in food systems - CGIAR GENDER Platform (CGIAR GENDER Impact Platform, 2020)
Achieving gender equality in food systems will help revitalize rural economies, increase food security and boost economic growth to reduce poverty. One of today’s biggest challenges is that millions of women remain mostly excluded from agricultural development through no fault of their own. They are unable to participate in the urgently needed transformation of food systems, essential to sustainably defeat hunger and produce enough, and good enough, food under the ongoing climate crisis.